2018
DOI: 10.7759/cureus.2426
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Knowledge and Attitudes of Medical and Dental Students towards HIV/AIDS in Pakistan

Abstract: The number of new human immunodeficiency virus (HIV) cases is increasing in Pakistan while it has seen a decline globally. A survey conducted recently has found that 132,000 people in Pakistan suffer from HIV. This study aims to check the levels of knowledge and attitudes about HIV/acquired immunodeficiency syndrome (AIDS) among medical and dental students.This cross-sectional study was designed and conducted at Combined Military Hospital Lahore Medical College and the Institute of Dentistry (CMH LMC) in Lahor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 11 publications
0
21
0
5
Order By: Relevance
“…3C) and Chesneya sect. Pulvinatae (Fig. 3D) are restricted to Tibet and adjacent regions, adapting to high-altitude psychrophytic habitats (Ali 1977; Zhu and Larsen 2010). The evolutionary history of Chesneya appears complex, whereas the elevation of the QTP and the subsequent aridifications may have played an important role (Meng et al 2015; Zhang et al 2015b), as in former Calophaca (Zhang et al 2015a), Caragana (Zhang and Fritsch 2010) and Hedysarum (Shue 1985; Duan et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…3C) and Chesneya sect. Pulvinatae (Fig. 3D) are restricted to Tibet and adjacent regions, adapting to high-altitude psychrophytic habitats (Ali 1977; Zhu and Larsen 2010). The evolutionary history of Chesneya appears complex, whereas the elevation of the QTP and the subsequent aridifications may have played an important role (Meng et al 2015; Zhang et al 2015b), as in former Calophaca (Zhang et al 2015a), Caragana (Zhang and Fritsch 2010) and Hedysarum (Shue 1985; Duan et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…[6] Studies have shown that the main transmission route of HIV/AIDS changes from injecting drug to sexual transmission, and the number of young students with HIV/AIDS increases year by year. [8] In this survey, our results indicated that the AIDS publicity and education work in universities has made some progress, while the students still had insufficient knowledge of AIDS prevention, the same as the result of Asad Ali and colleagues, [9] especially how to avoid the sexual transmission, for the reason that the awareness rate of knowing "Only to have sexual relations with a sexual partner can reduce the spread of AIDS" was only 76.9%. As sexual transmission is the main transmission route in Guizhou province, China, [10] therefore, the AIDS publicity and education in universities should be strengthened to improve their abilities to prevent and control AIDS.…”
Section: Discussionmentioning
confidence: 62%
“…The knowledge of MTCT of HIV and routes of transmission has been documented to be poor both in providers and recipients of care. 14…”
Section: Discussionmentioning
confidence: 99%